'A Shop Window Where You Can Choose the Goods You Like': Finnish industrial and trade fairs in the USSR, 1950s–1960s. Issue 2 (15th March 2018) - Kochetkova, Elena
Abstract : This article examines the Finnish industrial and trade fairs held in the Soviet Union in the context of Finnish–Soviet trade and scientific–technical cooperation in the 1950s and 1960s. While primarily focused on fairs, it also discusses different activities that accompanied them, such as lectures, visits, and negotiations between Finnish traders and Soviet officials and specialists. This study illustrates how such first-hand contact played an important role in Finnish–Soviet communications. First, they helped Finnish producers showcase their goods and technologies directly to Soviet buyers in various ministries and organizations. Second, these contacts included diverse activities such as face-to-face contacts, lectures, and seminars, being a means of technology transfer from Finland to the USSR . Finally, although they were commercial interactions without explicit ideological purposes – like many international exhibitions of the last century – Finnish fairs demonstrated a technological gap between Finland and the USSR.